Analysis Of Rooftop Skyshine Radiation Exposure With Angle Of Gantry Linear Accelerator 180° In Radiotherapy Unit Of Pertamina Central Hospital Jakarta - Mayarani Mayarani; Eka Putra Syarif Hidayat; Nursama Heru Apriantoro; Robert Kristian; Muhammad Irsal (Politeknik Kesehatan Kemenkes Jakarta II, 2018)
Principally, the measurement of skyshine radiation exposure is important to be conducted if there is public activity in a certain place in which the source of radiation can emit its scattering radiation to all directions including to the rooftop of a Radiotherapy building. the Regulation of the Head of the National Nuclear Power Energy No. 8 Year 2011 Article 32a and No. 4 year 2013 article 23a namely 1 mSv/year. As for the design of this research, it is quantitative descriptive by conducting the measurement of radiation exposure to 44 points of measurement, research instrumentations used herein are 2 surveymeter, water phantom, Linac Primus 2D Plus. Result radiation exposure measurement are 6 point areas with the values above 1 mR/hr. Each of the average value of the measurement of the exposure rate at each point is calculated by the annual dose formula. All the final calculation results with the annual dose formula in mSv/year unit yields the values below 1 mSv/year at the 44 points measurement. the rooftop area of Radiotherapy building through Child Polyclinic Pertamina Central Hospital is under a safe limit with all calculation results of annual dose values below 1 mSv/year.